Supervisi Pengawas Madrasah Terhadap Optimalisasi Kinerja Kepala Madrasah - Abdul Aziz (STIKes Ibnu Sina Ajibarang, 2023)
Academic supervision is a series of activities to help and guide teachers in developing their abilities to achieve learning goals. Academic supervision within the madrasah is carried out by the head of the madrasah. Madrasah principal supervision is the ability of the madrasah principal who carries out duties apart from being a leader in the school and also as a supervisor for teachers in carrying out evaluations and coaching aimed at developing the learning process for teachers. This research was carried out using a descriptive qualitative approach. Because it is carried out based on the current situation and circumstances. The results and discussion of the research show several results as follows: The madrasa head's academic supervision planning in optimizing tasks and functions has been arranged in prota and process but is not updated every year.